Nurses' Clinical Competence as a Predictor of Patient Safety Target Compliance in Surgical Procedures - Hani Tuasikal; Inge Dhamanti; Mahmudah Mahmudah; Nursalam Nursalam; Ah Yusuf; Ratna Dwi Wulandari; Hari Basuki Notobroto (Knowledge Dynamics, 2026)
Background: The implementation of patient safety goals in hospitals, including operating rooms, is inseparable from the competence of nurses. High levels of competence also contribute to improving the quality of nursing care and enhancing patient safety. This study aims to gain a deeper understanding of the relationship between the clinical competence of operating room nurses and the achievement of patient safety goals. Methods: This study used a cross-sectional design and collected data from seven private hospitals in Ambon City, with a sample of 66 surgical nurses. The sampling technique used was simple random sampling, a method of selecting participants from a population without regard to the strata within that population. Results: The clinical competence of surgical nurses was measured using three subdomains aligned with competency areas: ethical and legal professional practice and cultural sensitivity; nursing care provision and management; and personal and professional quality development. The frequency distribution of respondents was analyzed based on these clinical competence domains. There was a significant relationship between the clinical competence of surgical nurses and patient safety goals, particularly regarding surgical procedures. Conclusions: Clinical competence is a critical component of patient safety, as it helps ensure that nurses provide safe and effective care while promoting active involvement and participation in achieving patient safety goals.